A robust self-referenced 2D nyquist ghost correction for different MRI-biomarker measurements based on multi-band interleaved EPI - Liu, Xiaoxi; Chen, Shihui; Cui, Di; Hui, Edward S.; Chan, Queenie; Chen, Nan-Kuei; Chang, Hing-Chiu (Frontiers in Physics, 2023)
Purpose: To enable 2D Nyquist ghost correction for multi-band interleaved echo-planar imaging (EPI) without reference scan. Methods: 2D phase errors between positive and negative echo were directly measured from the multi-band interleaved EPI data acquired with alternating readout polarity, and then corrected by using multiplexed sensitivity encoding (MUSE) framework. The proposed method was tested on brain data acquired with and without multi-band imaging under different multi-shot factors (4, 8, and 16). In addition, the 2D phase corrections for the interleaved EPI data acquired with 2D zoomed-FOV, 2D reduced-FOV, or 3D multi-band imaging were also performed with the proposed method. The performance of our proposed method was assessed with single-to-noise ratio (SNR) and ghost-to-signal ratio (GSR), and then compared with an iterative 2D phase correction method. The g-factor penalty of the proposed 2D Nyquist ghost correction method associated with 2D phase error was also evaluated. The feasibility of the proposed method was evaluated in diffusion MRI and multi-echo fMRI where quantitative biomarkers with high quality are desired. Results: The proposed method successfully suppressed the ghost artifacts for the multi-shot interleaved EPI data acquired with different multi-shot factors, 2D and 3D multi-band acquisitions, zoomed-FOV, or reduced-FOV. Compared with the iterative method, our proposed method showed lower GSR and comparable SNR performance. Through g-factor penalty simulation, the proposed method showed less than 9% of overall SNR loss associated with a maximum y-linear phase error of π. The residual aliasing artifact was effectively eliminated in the quantitative biomarkers (ADC, FA and dynamic T2*) when applying the proposed method in diffusion imaging and multi-echo fMRI. Conclusion: The proposed method can perform robust 2D Nyquist ghost correction for multi-band multi-shot interleaved EPI without reference scan, and thus can be a generalized 2D ghost correction method for multi-shot interleaved EPI based acquisitions and applications.